Connectome to behaviour: modelling Caenorhabditis elegans at cellular resolution. (19th October 2018) - Larson, Stephen D.; Gleeson, Padraig; Brown, André E. X.
Abstract : It has been 30 years since the 'mind of the worm' was published in Philosophical Transactions B (White et al . 1986 Phil. Trans. R. Soc. Lond. B 314, 1–340). Predicting Caenorhabditis elegans ' behaviour from its wiring diagram has been an enduring challenge since then. This special theme issue of Philosophical Transactions B combines research from neuroscientists, physicists, mathematicians and engineers to discuss advances in neural activity imaging, behaviour quantification and multiscale simulations, and how they are bringing the goal of whole-animal modelling at cellular resolution within reach. This article is part of a discussion meeting issue 'Connectome to behaviour: modelling C. elegans at cellular resolution'.